2007
DOI: 10.1080/10610270600850036
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and physiological responses of fluent listeners while watching the speech of adults who stutter

Abstract: These data support the notion that stutter-filled speech can elicit physiological and emotional responses in listeners. Clinicians who treat stuttering should be aware that listeners show involuntary physiological responses to moderate-severe stuttering that probably remain salient over time and contribute to the evolution of negative stereotypes of people who stutter. With this in mind, it is hoped that clinicians can work with people who stutter to develop appropriate coping strategies. The role of amygdala … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 51 publications
5
45
0
Order By: Relevance
“…Coactivation has previously been associated with witnessing unpleasant stimuli such as surgery films (Palomba et al, 2000) and interestingly, when naïve listeners are first exposed to stuttering (Guntupalli et al, 2006(Guntupalli et al, , 2007Zhang et al, 2010). Based on his notions, we examined the current data for differential changes in HR and paradoxical relationship between SC and HR measures which might reflect anticipatory autonomic coactivation.…”
Section: Autonomic Coactivation?mentioning
confidence: 95%
“…Coactivation has previously been associated with witnessing unpleasant stimuli such as surgery films (Palomba et al, 2000) and interestingly, when naïve listeners are first exposed to stuttering (Guntupalli et al, 2006(Guntupalli et al, , 2007Zhang et al, 2010). Based on his notions, we examined the current data for differential changes in HR and paradoxical relationship between SC and HR measures which might reflect anticipatory autonomic coactivation.…”
Section: Autonomic Coactivation?mentioning
confidence: 95%
“…M. Silverman, 1976). In particular, a large number of studies have documented the negative attitudes of people who communicate with individuals who stutter (Collins & Blood, 1990;Guntupalli, Everhart, Kalinowski, Nanjundeswaran, & Saltuklaroglu, 2007;Hughes, Gabel, Irani, & Schlagheck, 2010;Panico, Healey, Brouwer, & Susca, 2005;Patterson & Pring, 1991;Susca & Healey, 2001;Woods & Williams, 1976). Although the cause of these negative attitudes may be multifactorial, many studies have shown an association between the severity of the presenting symptoms with the impressions of the communication partner (Altenberg & Ferrand, 2006;Blood, Blood, & Danhauer, 1978;Panico et al, 2005).…”
Section: Listener Impressions Among Communication Disordersmentioning
confidence: 97%
“…In the last approximately 60 years, based on the present authors’ review of the literature, there have been 12 published empirical studies of the association between skin conductance and stuttering (Adams & Moore, 1972; Berlinsky, 1954; Brutten, 1963; Dietrich & Roaman, 2001; Gray & Brutten, 1965; Gray & Karmen, 1967; Guntupalli, Everhart, Kalinowski, Nanjundeswaran, Saltuklaroglu, 2007; Kraaimaat, Janssen, Brutten, 1988; Jones et al, 2014b; Peters & Hulstjin, 1984; Reed & Lingwall, 1976, 1980; Weber & Smith, 1990). Eleven of these studies involved adults or adolescents who stutter (AWS), with only one, that present authors are aware of, that involved preschool-age children who stutter (Jones et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%